Tracking the Link Methodology around the world: Experiences by country - Castaño, Silvia-Elena; Mosquera, Erika (2023)
Summary of the main results of the LINK Methodology through the ArcGIS Storymap App.: https://storymaps.arcgis.com/stories/dfd0684f45ae4110875a67a5dd442831 (English) https://storymaps.arcgis.com/stories/a2a08ad34bcb4a3b99c300afdddff388 (Spanish)